(untitled) (Scientific journal of the Fergana State University, 2024)
Focusing the psychological characteristics of family members on the unity of the family for comfort in the family. For this, to demand responsibility from each other in meeting the needs of family members. This will definitely create peer pressure. As a result, each family member forms models that affect the family unit and family members change based on this model.